Pemetaan Daerah Rawan Banjir dengan Pemanfaatan Sistem Informasi Geografis pada Tiga Daerah Aliran Sungai (DAS) di Kawasan Ekonomi Khusus Mandalika - Budianto, Muh Bagus; Yasa, I Wayan; Agastya, Dewandha Mas; Saadi, Yusron; Pradjoko, Eko (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The Mandalika Special Economic Zone (SEZ) is currently a leading destination not only in Lombok but also in Indonesia. The presence of the Mandalika Circuit as a MotoGP race venue, along with the beauty of the coastal landscape and other tourism potential, makes Mandalika a Super Priority Destination. The Mandalika SEZ is located in three river basins, namely Tebelo Ngolang and Balak. Behind the splendor of the Mandalika Circuit and other supporting infrastructure lies a series of flood data that hit the area, including the floods of January 30, 2021, and December 23, 2022. Based on these events, a study is needed to map the flood risk in the three watersheds and the Mandalika SEZ. This flood risk map can later serve as a basis for formulating policies and anticipatory measures for future flooding. The required data includes rainfall data, land use maps, topographic maps, land use maps, slope maps, and geological/soil type data. The data were then analyzed using a Geographic Information System (GIS) and then overlaid using the ArcGIS software program. Based on the overlay results and weighting of the supporting factors for flooding, flood vulnerability at the study location can be determined. The results showed that the Tebelo Watershed is divided into 3 categories, namely a moderately vulnerable area of 270.32 ha, a vulnerable area of 479.89 ha and a very vulnerable area in the downstream area of 85.44 ha. The Ngolang Watershed is divided into two categories dominated by a vulnerable area of 930.97 ha and a moderately vulnerable area of 568.68 ha. Meanwhile, the Balak Watershed is divided into two categories, namely a vulnerable area of 1,418.59 ha and a moderately vulnerable area of 1,243.53 ha